PENGEMBANGAN OBJEK WISATA PANTAI PASIR TIKU KECAMATAN TANJUNG MUTIARA KABUPATEN AGAM - Ifzil Ivanly; paus iskarni (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
This reseach porpuse to obtain a strategy for developing the pasir tiku beach attractions that will be carried out in the future. This study uses a mix method of combination methods or methods from qualitative research with quantitative methods. This study uses a SWOT analysis to identify internal factors as supporters and inhibitors with identify external factors as a barrier and a incentive for the development of pasir tiku beach attractions. The results showed that the development strategy of Pasir Tiku Beach tourism object consisted of (1) resource development (2) tourism potential development (3) restructuring of existing facilities and infrastructure (4) adding facilities and infrastructure in accordance with tourist standards (5) establish cooperation with the government.